Literacy Of Sharia Selling And Buying Agreements At Dharma Wanita SMAN 1 Bangkinang City - Assyifa, Zubaidah; Khairi, Rifqil; Syaipudin, Muhammad; Mairiza, Diany; Hasda, Mifta; Lismawati, Lismawati; Amelia, Nur (Journal of Community Sustainability, 2024)
This service was carried out in Kampar Regency, Riau Province. The object is Dharma Wanita SMAN 1 Bangkinang Kota as one of the schools in Bangkinang Kota District. This service aims to socialize the Sharia Sale and Purchase Agreement in High Schools. The results of this service show that: 1) The success of the target number of training participants. 2) Achievement of activity goals. 3) Achievement of planned material targets. 4) Participants' ability to master the material. Overall, this service activity can be said to be successful. Apart from being measured by the four components above, this success can also be seen from the satisfaction of the participants after taking part in the activity because the service members provide the opportunity to ask as many questions as possible and when the service members ask questions they can be answered by the participants and they ask about the training agenda with the theme of the next sharia buying and selling contracts. This is because the theme/material of these sharia buying and selling contracts is interesting for participants.